2002
DOI: 10.1093/carcin/23.9.1463
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of mofezolac, a cyclooxygenase-1 selective inhibitor, on intestinal carcinogenesis

Abstract: Cyclooxygenase (COX)-2, one enzyme isoform responsible for producing prostanoids from arachidonic acid, contributes to colon carcinogenesis. Recently, genetic disruption of COX-1, the other isoform, was shown to decrease the number of intestinal polyps and prostaglandin E(2) levels in intestinal mucosa, like the case with COX-2 gene disruption, in Min mice. We therefore investigated whether a COX-1 selective inhibitor, mofezolac, suppresses intestinal carcinogenesis in rodents. F344 male rats, receiving azoxym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 13 publications
1
54
1
Order By: Relevance
“…C57BL/6-Apc Min/+ mice (Apc Min/+ mice) were purchased from The Jackson Laboratory. Apc 1309 and Apc Min/+ mice offspring were genotyped according to the method previously described (27,28) and recommendations of The Jackson Laboratory, respectively. Male mice were randomized into experimental and control groups and were fed standard laboratory chow and tap water ad libitum.…”
Section: Animalsmentioning
confidence: 99%
“…C57BL/6-Apc Min/+ mice (Apc Min/+ mice) were purchased from The Jackson Laboratory. Apc 1309 and Apc Min/+ mice offspring were genotyped according to the method previously described (27,28) and recommendations of The Jackson Laboratory, respectively. Male mice were randomized into experimental and control groups and were fed standard laboratory chow and tap water ad libitum.…”
Section: Animalsmentioning
confidence: 99%
“…14 Moreover, we recently demonstrated that mofezolac, a COX-1 selective inhibitor, suppressed the development of azoxymethane (AOM)-induced colonic aberrant crypt foci (ACFs), putative preneoplastic lesions in F344 rats and intestinal polyp development in mice with a truncated Apc gene at codon 1309 (APC1309 mice). 15 It should be noted that prostaglandin E 2 (PGE 2 ) levels were increased in intestinal polyps in Min mice compared with surrounding normal tissue, and genetic disruption of the COX-1 gene, as well as the COX-2 gene, indicated that both isoforms contributed to PGE 2 production. 14 PGE 2 exerts its biologic actions through binding to the 4 specific membrane receptor subtypes EP 1 , EP 2 , EP 3 and EP 4 .…”
Section: Abstract: Apc Knockout Mice; Cox-1 Selective Inhibitor; Coxmentioning
confidence: 99%
“…15,23 Mice at 7 weeks of age were randomized into experimental and control groups. The animals were housed 2 or 3 to a plastic cage in a holding room controlled at 24 Ϯ 2°C and at 55% relative humidity with a 12/12-hr light-dark cycle.…”
Section: Animals and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mofezolac ([3,4-di(4-methoxyphenyl)-5-isoxazolyl] acetic acid) (Kitamura et al, 2002) was a gift from Yoshitomi Pharmaceutical Corporation. (Tokyo, Japan).…”
Section: Chemicals and Other Materialsmentioning
confidence: 99%